ICLAS Working Group on Harmonization: International guidance concerning the production care and use of genetically-altered animals. (July 2013) - Rose, M; Everitt, J; Hedrich, H; Schofield, J; Dennis, M; Scott, E; Griffin, G
Replacement, Reduction and Refinement, the 'Three Rs' of Russell & Burch, are accepted worldwide as fundamental to the ethics of animal experimentation. The production, care and use of genetically-altered animals can pose particular challenges to the implementation of the Three Rs, 1 necessitating additional considerations by those responsible for overseeing the ethical use and appropriate care of animals involved in science. The International Council for Laboratory Animal Science brings representatives of the international laboratory animal science community together to recommend acceptance of guidance documents. The harmonization of guidance concerning genetically-altered animals was seen as a priority because of the increasing globalization of research involving these animals.